Sustainable Marketing Strategy Optimization: Analysis Of The Role Of Green Branding In Improving Consumer Preference - Nengsih, Widya (Jurnal Ilmu Sosial Mamangan, 2025)
Sustainable marketing has become a major focus for companies in the modern era, especially with increasing consumer awareness of environmental issues. This article analyzes how green branding can be used to increase consumer preferences and strengthen their loyalty to brands. Based on an analysis of literature over the last 10 years, this research reveals that environmentally oriented marketing strategies not only improve brand image but also create stronger emotional connections between consumers and brands. This study uses secondary data from various global studies to support the argument. In addition, this article also highlights the challenges companies face in implementing environmentally friendly marketing strategies. By providing practical guidance for optimizing green branding, this research contributes to the sustainable marketing literature and provides strategic insights for business people.